Role of seminal plasma in maintaining quality of ram epididymal spermatozoa preserved at low temperature (3â5oC) - Rizal, Muhammad; Surachman, Maman; ., Herdis; Aku, Achmad Selamet (Indonesian Journal of Animal and Veterinary Sciences, 2006)
Cauda epididymal spermatozoa could be used as an alternative source of gamete in the application of various reproductive technologies, because the spermatozoa is motile and has ability of fertilizing the oocyte. The purpose of this research was to examine the effect of addition of seminal plasma on the quality of ram cauda epididymal spermatozoa preserved at 3â5oC. Collected-spermatozoa was divided into five parts then centrifuged at 3,000 rpm for 30 min and the supernatant was removed. One-fifth was diluted with Tris extender (Tris) and the remaining was added 0.5 ml ram seminal plasma then diluted with Tris extender (PS-Tris), 15% AndroMed + 85% distilled water (PS-AM15), 20% AndroMed + 80% distilled water (PS-AM20), and 25% AndroMed + 75% distilled water (PS-AM25), respectively. Quality of collected-spermatozoa including spermatozoa concentration (SC), percentages of motile spermatozoa (MS), live spermatozoa (LS), abnormal spermatozoa (AS), cytoplasmic droplet (CD), and intact plasma membrane (IPM) were evaluated. Percentages of MS, LS, and IPM of diluted-spermatozoa was evaluated every day during preserved at 3â5oC for three days. Results of this study showed that mean SC, MS, LS, AS, CD, and IPM of fresh spermatozoa were 11,660 million/ml, 65, 81, 7.6, 10.2, and 82.2%, respectively. Addition of seminal plasma in cauda epididymal spermatozoa prior to dilution could maintain the quality of spermatozoa during preserved at 3â5oC for three days. At day-4 of storage, percentages of MS, LS, and IPM for PS-Tris (43, 58, and 59.2%), PS-AM20 (40.5, 53.75, and 53.75%), and PS-AM25 (40, 54.8, and 55.2%) were significantly (P<0.05) higher than Tris (21, 34.8, and 33.6%) and PS-AM15 (20, 40, and 42.2%). In conclusion, addition of seminal plasma in ram cauda epididymal spermatozoa prior to dilution with Tris or 20 and 25% AndroMed extenders could maintain the quality of spermatozoa during preserved at 3â5oC for three days, and could be used for artificial insemination or in vitro embryo production programs. Key Words: Cauda Epididymal Spermatozoa, Seminal Plasma, Tris, AndroMed, Ram